Theory into practice: Applying design for sustainable behaviour to drive single use cup recycling. (2nd January 2023) - Lilley, Debra; Lofthouse, Vicky
Abstract: This paper introduces a real-world, case study application of a Design for Sustainable Behaviour (DfSB) process model and associated evaluation criteria towards the collection of single use cups for recycling at x. It concludes that strategy selection criteria need to be contextualised to ensure meaning and relevance; that framing criteria as prompting questions encourages discussion and reflection, and that engagement with multiple stakeholders when selecting strategies is vital. It also underlines the importance of ethical considerations when implementing behaviour change interventions within the public domain, and mindfulness of potential 'rebound effects'.